Efektivitas Pengembangan Media Pembelajaran Komik Berbasis Kodular untuk Kemampuan Pemahaman Literasi Matematika Siswa SDS Edustar - Nailul Himmi Hasibuan; Yessy Gusmania; Silvia Rahman (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2022)
Students do not understand the basic concepts of mathematics. Even understanding mathematics lessons in class is still difficult, let alone solving mathematical literacy problems. This is due to the lack of learning media facilities that support mathematics literacy learning. So that due to a lack of understanding of the concepts of mathematics, and considers mathematics lessons are boring lessons. Therefore, it is necessary to develop flexible teaching materials that can be used in any situation to support students' understanding of mathematical literacy. Thus, the researcher developed a codular-based comic learning media for students' mathematical literacy comprehension skills. This study aimed to see the effectiveness of the codular-based comics learning media for the ability to understand mathematical literacy of elementary school students Edustar. This research was conducted at SDS Edustar Batam with research subjects in grades 4, 5, and 6. The data collection of this study used the results of the post-test of students on students' mathematical literacy of 62.01%. So it can be concluded that the codular-based comics learning media is effectively used as a medium for learning students' mathematical literacy.